Dietary intake of carbohydrates and risk of type 2 diabetes: the European Prospective Investigation into Cancer-Norfolk study. Issue 2 (28th January 2014) - Ahmadi-Abhari, Sara; Luben, Robert N.; Powell, Natasha; Bhaniani, Amit; Chowdhury, Rajiv; Wareham, Nicholas J.; Forouhi, Nita G.; Khaw, Kay-Tee
<x content-type="archive" xml:space="preserve">Abstract</x> In the present study, we investigated the association between dietary intake of carbohydrates and the risk of type 2 diabetes. Incident cases of diabetes (n 749) were identified and compared with a randomly selected subcohort of 3496 participants aged 40–79 years. For dietary assessment, we used 7 d food diaries administered at baseline. We carried out modified Cox proportional hazards regression analyses and compared results obtained from the different methods of adjustment for total energy intake. Dietary intakes of total carbohydrates, starch, sucrose, lactose or maltose were not significantly related to diabetes risk after adjustment for confounders. However, in the residual method for energy adjustment, intakes of fructose and glucose were inversely related to diabetes risk. The multivariable-adjusted hazard ratios (HR) of diabetes comparing the extreme quintiles of intake were 0·79 (95 % CI 0·59, 1·07; P for trend = 0·03) for glucose and 0·62 (95 % CI 0·46, 0·83; P for trend = 0·01) for fructose. In the nutrient density method, only fructose was inversely related to diabetes risk (HR 0·65, 95 % CI 0·48, 0·88). The replacement of 5 % energy intake from SFA with an isoenergetic amount of fructose was associated with a 30 % lower diabetes risk (HR 0·69, 95 % CI 0·50, 0·96). Results of the standard and energy partition methods were similar to those of the residual method. These prospective findings suggest that the intakes of starch and sucrose are not associated, but that those of fructose and glucose are inversely associated with diabetes risk. Whether the inverse associations with fructose and glucose reflect the effect of substitution of these carbohydrate subtypes with other nutrients (i.e. SFA), their net higher intake or other nutrients associated with their intake remains to be established through further investigation.